Congress of Neurological Surgeons Systematic Review and Evidence-Based Guideline for the Management of Patients With Residual or Recurrent Nonfunctioning Pituitary Adenomas. Issue 4 (1st October 2016) - Sheehan, Jason; Lee, Cheng-Chia; Bodach, Mary E.; Tumialan, Luis M.; Oyesiku, Nelson M.; Patil, Chirag G.; Litvack, Zachary; Zada, Gabriel; Aghi, Manish K.
Abstract: BACKGROUND: Despite the advancement of microsurgical and endoscopic techniques, some nonfunctioning pituitary adenomas (NFPAs) can be difficult to cure. Tumor recurrence or incomplete resection may occur in some patients with NFPAs, and management strategies for these NFPAs remain unclear. OBJECTIVE: To review the existing literature as it pertains to the management of postsurgical residual or recurrent NFPAs. METHODS: A systematic review of the treatment options for residual or recurrent NFPAs was performed. In this review, the authors critically evaluated the evidence to support the options of repeat microsurgical resection, stereotactic radiosurgery (SRS), stereotactic radiotherapy (SRT), and fractionated radiation therapy (XRT). RESULTS: Forty-nine studies met the inclusion criteria for analysis: outcome of repeat surgical resection (n = 4), radiosurgery (ie, single-session or hypofractionated SRS; n = 24), or fractionated radiotherapy (ie, conventional XRT, proton beam radiotherapy, intensity-modulated radiotherapy, SRT; n = 21). No class I evidence was available; 6 studies met criteria for class II evidence; and other studies provided class III evidence. A meta-analysis of 5 class II studies with recurrence rates for both adjuvant radiation therapy and observation demonstrated that XRT for residual/recurrent NFPAs offered a lower rate of recurrence (odds ratio = 0.04; 95% confidence interval, 0.01-0.20; P < .001). The analysis also demonstrated significant heterogeneity between the included studies (χ 2 = 20.70; P = .003; I 2 = 81%). CONCLUSION: Repeat resection, SRS, SRT, and XRT play a role in the management of patients with recurrent or residual NFPAs. SRS or some type of radiation therapy is typically performed for patients with residual tumor or tumor recurrence after resection. The full guidelines document for this chapter can be located at https://www.cns.org/guidelines/guidelines-management-patients-non-functioning-pituitary-adenomas/Chapter_7 .